Voda in zdrav način življenja - Golob, Nika; Mlakar, Suzana; Ambrožič Dolinšek, Jana (Revija za elementarno izobraževanje, 2011)
Water and a healthy way of living. During mandatory education, Slovenian primary school students are often encouraged to drink adequate amounts of water. Increasing numbers of researchers are finding that consuming larger amounts of non-alcoholic carbonated and noncarbonated beverages and fruit beverages causes an increased intake of energy, which can increase the risk of obesity in children and adolescents. As the majority of studies on drinking habits in Slovenia and abroad were carried out on secondary school populations, we decided to focus our research on primary school pupils and their parents. We were interested whether there are differences in their choice of beverage in regard to school grade and gender. Our results show that the pupils who were polled live less healthy lifestyles. This usually becomes evident during the sixth grade of primary school - when the pupils reach the age of 11 and 12. A factor that has to be considered is the lifestyle of the parents, whose influence on the children is especially evident in the amount of physical activity they participate in and their breakfast habits. We propose that schools should consider developing policies to reduce the availability of less-healthy choices in vending machines, to reduce access to beverage vending machines and to promote drinking healthy water.
Keywords: drinking water; healthy lifestyle; perants' influence; school factors